Microplastic Pollution In The Aquaculture Field: A Mini Review - Ahmad, Khamsiah; Recar, Yuliana; Inayah, Inayah; Syazili, Aras; Ridwan, Mutmainnah; Abu, Nur; Galib, Marliani (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
Plastic pollution has become pervasive in aquatic environments, emerging as a significant ecological concern over the past decade. Plastic debris varies in size, from large fragments to microplastics—particles less than 5 mm in diameter—that result from the primary (manufacturing production) and secondary (degradation from larger plastics) sources. In aquaculture systems, these microplastics can accumulate in both the environment and within aquatic organisms, as their decomposition is a prolonged process. The persistence of microplastics poses risks to biota, including potential physical harm and chemical exposure. This review discusses current research on the presence and impact of microplastics in aquaculture, highlighting the negative effects observed. The findings indicate that microplastics represent an escalating threat to aquaculture systems, necessitating periodic monitoring and the standardisation of analytical methods to manage and mitigate their impact effectively.​